Margret and H.A. Rey's Curious George makes pancakes - Rey, H. A. (Hans Augusto), 1898-1977.; Rey, Margret; Vipah Interactive (Boston : Houghton Mifflin, 1998)
Curious George, an inquisitive monkey, causes quite a stir when he tries his "hand" at making pancakes at a fundraiser for the children's hospital.
Based on the original character by Margret and H.A. Rey.
L.A. Recommended Foreign Language
4.0
K-3
Keywords: Curious George (Fictitious character) -- Fiction; Fund raising -- Fiction; Monkeys -- Fiction; Pancakes, waffles, etc. -- Fiction